Link with Latin America. - MANNING, Patrick (1994)
Discusses the 1993 Agreement on Trade and Investments between CARICOM and Venezuela, the 1989 Trinidad and Tobago/Venezuela partial Scope Agreement, and the 1992 Agreement between the Royal Bank of Trinidad and Tobago and the Andean Development Fund. Notes that these agreements allow access by Caribbean businessmen to the markets of Venezuela and the Andean Group.